Size and Concentration of Extracellular Vesicles in Pancreatic Juice From Patients With Pancreatic Ductal Adenocarcinoma. Issue 3 (18th March 2022) - Nesteruk, Kateryna; Levink, Iris J.M.; Dits, Natasja F.J.; Cahen, Djuna L.; Peppelenbosch, Maikel P.; Bruno, Marco J.; Fuhler, Gwenny M.
Abstract : INTRODUCTION: Extracellular vesicles (EVs) and their cargo may provide promising biomarkers for the early detection of pancreatic ductal adenocarcinoma (PDAC). Although blood-borne EVs are most frequently studied as cancer biomarkers, pancreatic juice (PJ) may represent a better biomarker source because it is in close contact with the ductal cells from which PDAC arises. It is, as yet, unknown whether PDAC results in a distinct type or increased number of particles in PJ and whether this has diagnostic value. METHODS: Secretin-stimulated PJ was collected from the duodenum of 54 cases and 117 nonmalignant controls under surveillance for PDAC. Serum was available for a subset of these individuals. The vesicular composition of these biofluids was analyzed with nanoparticle tracking analysis. RESULTS: The concentration of EVs did not differ between controls and PDAC cases. However, a higher number of large vesicles were found in PJ (but not serum) for patients with PDAC compared with controls. DISCUSSION: The composition of isolated EVs from PJ, but not serum, is altered in patients with PDAC. This suggests that PJ may carry disease-specific markers not present in serum and provides a valuable biomarker source for PDAC diagnosis. The nature of the larger particles in EV isolates from PJ of PDAC cases requires further investigation.